Time Recommendation and Alternative Parameters for Severe Maxillofacial Trauma Reconstruction - Indri Lakhsmi Putri1, Magda Rosalina Hutagalung1, Ida Bagus Narmada2, David Sontani Perdanakusuma1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Severe maxillofacial trauma often associated with other injuries, therefore the delay of reconstruction often occur until the patients are stable. Early reconstruction results a better facial function and appearances. Aim: The aim of this study to give the recommendation and alternative parameters for severe maxillofacial trauma reconstruction. Methods: The method of this study is adult patients with bimaxillary and bilateral maxillofacial trauma were eligible for this study, while pregnant women were excluded. Nine patients with maxillofacial trauma were involved in this study and we measured 15 facial anthropometric and 41 lateral cephalometricon 7, 14, 21 days compared to 3 months post-reconstruction. Results: The result of this study showed reconstruction can be planned 14 days after trauma for lower jaw fracture and 21 days after bimaxillary fracture. Lateral cephalometry was a reliable method to measure facial edema following surgery which combined facial anthropometry with lateral cephalometry using parameters that are not affected by edema. This can be applied as an additional guiding tool in surgical planning for maxillofacial trauma patients especially those with bimaxillary and bilateral fractures. Conclusion: Combination of anthropometric and cephalometric parameters which are not affected by edema can be applied as an additional guiding tool in surgical planning for maxillofacial trauma patients.